Nitrogen-Doped TiO2 Nanotube Arrays with Enhanced Photoelectrochemical Property. (2nd May 2012) - Li, Shipu; Lin, Shiwei; Liao, Jianjun; Pan, Nengqian; Li, Danhong; Li, Jianbao
Abstract : N-doped TiO2 nanotube arrays were prepared by electrochemical anodization in glycerol electrolyte, followed by electrochemical deposition in NH4 Cl solution. An orthogonal experiment was used to optimize the doping conditions. Electrolyte concentration, reaction voltage, and reaction time were the main factors to influence the N-doping effect which was the determinant of the visible range photoresponse. The optimal N-doping conditions were determined as follows: reaction voltage is 3 V, reaction time is 2 h, and electrolyte concentration is 0.5 M. The maximal photocurrent enhanced ratio was 30% under white-light irradiation. About 58% improvement of photocatalytic efficiency was achieved in the Rhodamine B degradation experiment by N doping. The kinetic constant of the N-doped TNT arrays sample was almost twice higher than that of the undoped sample. Further analysis by X-ray photoelectron spectroscopy supported that electrochemical deposition is a simple and efficient method for N doping into TiO2 nanotube arrays.